ANALISIS KEMAMPUAN PENALARAN INDUKTIF MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS PAPUA - Drupadi, Septian Woro; Mumu, Jeinne (Universitas Papua, 2018)
This research was conducted to analyze the mathematical Inductive reasoning abilities of studentsâ€™ mathematics education UNIPA. Research on inductive mathematical reasoning skills using qualitative methods using observation techniques, tests and interviews. The results showed that the mathematical inductive reasoning abilities of mathematics education students UNIPA were mostly in the moderate category. Students' inductive reasoning ability on each indicator is the ability to present mathematical statements in writing or drawings of 66.66%, the ability to submit suspicions by 26.66%, mathematical manipulation ability of 29.44%, ability to compile evidence, provide reasons or evidence for some solutions of 5.82%, finding patterns or traits of mathematical symptoms to generalize of 30.27%, examining validity of arguments 11.32% and drawing conclusions from statements of 5.27%.Â DOI:Â https://doi.org/10.30862/jhm.v1i2.1048